Correlation between the liver transection line localization and future liver remnant hypertrophy in associating liver partition and portal vein ligation for staged hepatectomy - Romic, Ivan; Augustin, Goran; Pavlek, Goran; Kresic, Elvira (Frontiers in Surgery, 2024)
Colorectal liver metastases (CRLMs) represent the most prevalent form of secondary liver tumors, and insufficient future liver remnant (FLR) often leads to unresectability. To tackle this challenge, various methods for stimulating liver hypertrophy have been developed including portal vein embolization (PVE), associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) and the newest one, liver venous deprivation (LVD). ALPPS was thoroughly studied over the last decade and it has been shown to induce rapid and intensive FLR hypertrophy. The objective of this study was to assess whether the localization of the liver transection line during the initial stage of ALPPS correlates with the degree of FLR hypertrophy.A retrospective, multicentric study was conducted, and we analyzed all consecutive patients with CRLMs who underwent ALPPS over the eight-year period. Patients were categorized into two groups based on the type of resection -right trisectionectomy (ERH) or right hemihepatectomy (RH) respectively. The degree of hypertrophy (DH), its correlation with FLR and postoperative outcomes were assessed.The cohort consisted of 136 patients (72 in the ERH group and 64 in the RH group). Baseline characteristics, hypertrophy interval, and total liver volume showed no significant differences between the groups. DH was greater in the ERH group (83.2% vs. 62.5%, p= 0.025). A strong negative correlation was observed between FLR volume and DH in both groups. Postoperative outcomes and one-year survival were comparable between the groups.FLR hypertrophy is influenced by the localization of the liver transection line in ALPPS. Furthermore, correlation analysis indicated that a smaller estimated FLR is associated with greater DH. No statistical difference in outcomes was noted between the groups.